18F-FDG-PET Detects Drastic Changes in Brain Metabolism in the Tg4–42 Model of Alzheimer’s Disease - Bouter, Caroline; Henniges, Philipp; Franke, Timon N.; Irwin, Caroline; Sahlmann, Carsten Oliver; Sichler, Marius E.; Beindorff, Nicola; Bayer, Thomas A.; Bouter, Yvonne (Frontiers in Aging Neuroscience, 2019)
The evaluation of new therapeutic strategies in Alzheimer’s disease relies heavily on in vivo imaging and suitable animal models that mimic the pathological changes seen in patients. 18F-FDG-PET is a well-established non-invasive imaging tool for monitoring changes in cerebral brain glucose metabolism in vivo. 18F-FDG-PET is used as a functional biomarker for Alzheimer’s disease as patients show an early and progressive reduction of cerebral glucose metabolism. However, earlier studies in preclinical models of Alzheimer’s disease showed conflicting results. The aim of this study was the evaluation of cerebral glucose metabolism in the Tg4-42 mouse model of Alzheimer’s disease using 18F-FDG-PET/MRI. Tg4-42 mice show an age-dependent reduction in glucose metabolism together with severe neuron loss and memory deficits. Similar to Alzheimer’s patients early decrease in 18F-FDG uptake was already detected in young (3 months) Tg4-42 mice. The altered glucose metabolism coupled with age- and disease related cognitive decline of Tg4-42 mice make it a well-suited model for preclinical testing of Alzheimer-relevant therapeutics.